Pada Ibu yang Mengalami Baby Blues Syndrome - Hasjanah, Yusrita (Universitas Ahmad Dahlan, 2014)
AbstractThis research aims to know the impact of coping that are used as well as coping with being used. The research method used was qualitative research with the phenomenology of approach. The subject in this study are two people who have experienced mother baby blues syndrome. The techniques of data collection in this research conducted a structure interview session. The results showed that mother who experienced baby blues syndrome used problem focused coping. Problem focused coping includes problem solving planfull, information seeking, seeking assistance, and direct action. They also ever used the emotional focused coping included self critism, and positive reappraisal. The benefits of using coping strategy is make the subject become more understanding about her mood swings condition after delivery, as well as achieved more knowledge about their condition.Keywords: Coping, Baby Blues Syndrome